Relationship between obesity index and cardiovascular risk in primary care patients on Crete, Greece: a data driven sub-analysis - Bechraki, L.; Anastasaki, M.; Papadakis, S.; Linardakis, M.; Anyfantakis, D.; Lionis, C.; Symvoulakis, E. K. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The present sub-analysis aimed to examine the relationship between obesity index and cardiovascular risk among primary care attendees. Study design. Stratified random sampling was previously used to recruit general practitioners, practicing on Crete island, Greece, whose patients were then enrolled. Methods. Initial sample included 815 primary care attendees (55.7% women; mean age 65.2 years; range 40–98 years). Due to missing values regarding 13 participants, data from 802 patients were included for the current analysis. Body measurements (weight, height), among other bio-clinical parameters, were recorded upon practice visit. The 10-year cardiovascular disease risk was estimated using the European Society of Cardiology (and other societies), 10-year Systematic Coronary Risk Estimation and multivariate linear regression was used to assess relationships between Obesity Index and cardiovascular disease risk. Results. Higher risk is shown to be significantly related with male gender, older age, unemployed/retired status, urban area of living or smoking (p<0.05), as well as with higher levels of obesity index (stand. beta=0.048, p=0.028). Conclusions. Obesity Index may be useful for cardiovascular disease risk prediction and correction at the primary care settings, since obesity is easily addressed during the first medical contact.